2020 Working Conference on Software Visualization (VISSOFT) 2020
DOI: 10.1109/vissoft51673.2020.00006
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Evolution of Component-Based Software Architectures in Virtual Reality

Abstract: The visualization of software architectures by the use of effective and feasible visual metaphors provides an intuitive approach to comprehend the implemented architecture of a software project. In this regard not only the visualization of the latest status of the implemented architecture is important, but also the visualization of the history of software architectures. Such visualizations show dependencies and contexts in which design decisions were made. Resulting information supports programmers to understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Many software visualization tools exist that present a system's architecture [5], [6], both in 2D (e.g., Polymetric Views [7], Samoa [8], Softwarenaut [9], Beck et al [10]) and 3D (e.g., Balzer and Deussen [11], IslandViz [12], ExplorViz [13], CityVR [14], CodeCity [15]). Experiments showed that using a well-constructed 3D software visualization is more effective than using an IDE in terms of correctness and completion time for software comprehension tasks [15].…”
Section: State Of the Artmentioning
confidence: 99%
See 1 more Smart Citation
“…Many software visualization tools exist that present a system's architecture [5], [6], both in 2D (e.g., Polymetric Views [7], Samoa [8], Softwarenaut [9], Beck et al [10]) and 3D (e.g., Balzer and Deussen [11], IslandViz [12], ExplorViz [13], CityVR [14], CodeCity [15]). Experiments showed that using a well-constructed 3D software visualization is more effective than using an IDE in terms of correctness and completion time for software comprehension tasks [15].…”
Section: State Of the Artmentioning
confidence: 99%
“…Metaphors for 3D software visualization can be divided into abstract metaphors (e.g., 3D graphs [11], [19], [20]) and realworld metaphors (e.g., city metaphor [14], [15], [17], island metaphor [12], or solar metaphors [21]- [24]). A metaphor has to be expressive enough to describe different abstraction levels without breaking while letting users transition between these.…”
Section: State Of the Artmentioning
confidence: 99%
“…2D metaphors are mostly abstract graphs, trees, and diagrams [2,12,23]. 3D metaphors borrow analogies from the physical world to exploit viewers' familiarity with real-world constructs, e.g., cities, islands, or planets [1,8,10,13,17,26,28]. 3D software visualizations can be distinguished by the medium they employ, i.e., computer screens, augmented reality, or virtual reality [16,18].…”
Section: Software Visualizationmentioning
confidence: 99%
“…of structural system aspects, is essential for gaining an overview of a system's architecture [6,11]. However, existing software visualization [1,8,10,17,28] is hampered by a pivotal problem: The structural visualizations of different parts of a software system are hard to differentiate due to repetitive and complex patterns in the visual representation that cannot easily be distinguished (see Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…It is essential to detect software architecture (SA) problems before software development, but it is not easy to analyze SA because of software heterogeneity and the arrangement of software components [ 1 , 2 ]. Consequently, the problematic SA leads to project failure; therefore, different big, upfront designs are sketched based on the experiences of software analysts to explore the SA problems in the early phase [ 3 ].…”
Section: Introductionmentioning
confidence: 99%